STUDENTS PERSPECTIVES ON THE ROLE OF OPEN ACCESS CENTRE AND LANGUAGE LABORATORY AS SUPPORTING UNITS IN DEVELOPING ENGLISH LANGUAGE SKILLS - Wuryani Hartanto (Celt: A Journal of Culture, English Language Teaching & Literature, 2014)
This study aims at revealing the perception of the 2010, 2011 and 2012 academic year studentsof the Faculty of Letters on two supporting units at the faculty, namely Open Access Centre (OAC) and Language Laboratory (LL) in enhancing their English Language Skills. The results show that the average students consider both OAC and LL useful in developing their English Language competence. On the whole, they are satisfied with the existence of these two media except for a few things which need improving, such as facilities and instruments.